ANALYSIS OF CUSTOMER PROTECTION IN BANKING CREDIT AGREEMENTS IN INDONESIA - Muhamad Agung Dharmajaya (INFOKUM, 2019)
This study aims to analyze the forms of legal protection for customers (debtors) in bank credit agreements in Indonesia, as well as the obstacles encountered in their implementation. Credit agreements often take the form of standard contracts, which tend to place customers in a weaker bargaining position compared to banks. This study uses a normative method with a statutory and conceptual approach, analyzing the legal principles of agreements and regulations related to consumer protection in financial services. Customer-debtor protection is divided into preventive protection through restrictions on bank freedom of movement based on Article 18 of the Consumer Protection Law and the Financial Services Authority (OJK) transparency regulations, which threaten to render exoneration clauses null and void (van rechtswege nietig). Repressive protection is available through lawsuits for Unlawful Acts or Abuse of Circumstances (misbruik van omstandigheden) in court, as well as non-litigation channels through the Alternative Dispute Resolution Agency for the Financial Services Sector (LAPS SJK). However, the OJK's supervisory function is considered ineffective in practice due to its reactive, complaint-based nature, limited supervisory human resources, high information asymmetry, and lenient administrative sanctions that have not yet provided a deterrent effect for the banking industry. Conclusion: While legal instruments for customer protection are well-structured, enforcement of the principle of contractual balance remains weak in practice. The OJK needs to transform its supervisory system into a digital-proactive one, utilizing artificial intelligence-based supervisory technology (SupTech) (AI Contract Review) to screen draft bank contracts en masse and strengthen sanctions in the form of product license suspensions for banks that violate this principle.